Acute arterial occlusive disease due to tumor thrombus from lung metastasis of breast cancer with cartilaginous and osseous metaplasia: a case report - Ayana Sato; Akiko Matsumoto; Saki Naruse; Yuka Isono; Yuka Maeda; Miki Yamada; Tatsuhiko Ikeda; Yuko Sasajima; Hiromitsu Jinno (Surgical Case Reports)
Abstract Background Tumor embolization due to venous infiltration of breast cancer pulmonary metastases is very rare. Case presentation A 72-year-old female was diagnosed with triple-negative breast cancer. Neoadjuvant chemotherapy was discontinued because of progressive disease, and a right mastectomy with sentinel lymph node biopsy was performed. The pathological analysis of surgical specimens revealed carcinoma with cartilaginous and/or osseous metaplasia. At 22 months after surgery, lung metastasis was observed, and 6 months after initiating treatment for lung metastases, she complained of sudden numbness in the left-lower limb with trouble walking. Ultrasonography showed an embolism in the left popliteal artery, and contrast computed tomography showed enlarged lung metastases and infiltration of the left-upper lobe disease into the left superior pulmonary vein and left atrium. Acute arterial occlusive disease in the left-lower limb caused by the tumor embolism was suspected, so an endovascular thrombectomy was performed. Tumor emboli were removed by embolectomy catheter. Conclusion This report of lung metastasis from breast cancer with cartilaginous and/or osseous metaplasia and acute lower-limb artery occlusion due to a tumor thrombus adds useful information to the literature on these extremely rare cases.